Salvianolic Acid B Improves Chronic Mild Stress-Induced Depressive Behaviors in Rats: Involvement of AMPK/SIRT1 Signaling Pathway - Liao D (Dove Medical Press, 2020)
Dehua Liao,1,2,* Yun Chen,1,* Yujin Guo,3 Changshui Wang,4 Ni Liu,1 Qian Gong,1 Yingzhou Fu,1 Yilan Fu,1 Lizhi Cao,1 Dunwu Yao,1 Pei Jiang3 1Department of Pharmacy, Hunan Cancer Hospital, Changsha, Hunan 410013, People’s Republic of China; 2Department of Pharmacy, Second Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 3Institute of Clinical Pharmacy & Pharmacology, Jining First People’s Hospital, Jining, Shandong 272000, People’s Republic of China; 4Department of Clinical Translational Medicine, Jining Life Science Center, Jining, Shandong 272000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pei Jiang Tel/ Fax + 86 537 2106208Email jiangpeicsu@sina.comIntroduction: Depression is one of the most common neuropsychiatric illnesses which leads to a huge social and economic burden on modern society. So, it is necessary to develop an effective and safe pharmacological intervention for depression. Accumulating evidence has shown that adenosine monophosphate-activated protein kinase/sirtuin 1 (AMPK/SIRT1) signaling pathway plays a pivotal role in the development of depression. Our present study aimed to investigate the antidepressant effect and possible mechanisms of salvianolic acid B (SalB) in a chronic mild stress (CMS)-induced depression model in rats.Materials and Methods: The rats were randomly divided into three groups: control group with no stressor, CMS group and CMS+SalB (30 mg/kg/d) group. After administration for 28 consecutive days, the behavior tests were performed. The rats were sacrificed after behavior tests, and the brain tissues were collected for biochemical analysis.Results: It was observed that the administration of SalB for 28 consecutive days successfully corrected the depressive-like behaviors in CMS-treated rats. SalB could effectively reduce the gene expression of pro-inflammatory cytokines such as interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor α (TNF-α), as well as nuclear factor-kappa B (NF-κB) p65 protein. In addition, inhibitor of NF-κB (IκB) protein expression was significantly increased after the administration of SalB. Moreover, SalB could effectively decrease protein expression of oxidative stress markers such as 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) and increase the activity of catalase (CAT). SalB treatment also reversed CMS-induced inhibition of Nrf2 signaling pathway, along with increasing the mRNA expression of NAD(P)H:quinone oxidoreductase (NQO-1) and heme oxygenase 1 (HO-1). Regarding the endoplasmic reticulum (ER) stress markers, the protein expressions of C/EBP-homologous protein (CHOP) and glucose-regulated protein 78 kD (GRP78) were also significantly reduced after SalB administration. Furthermore, the supplementation of SalB could effectively activate the AMPK/SIRT1 signaling pathway, which indicated significant increase in pAMPK/AMPK ratio and SIRT1 protein expression.Conclusion: Our study demonstrated that SalB relieved CMS-induced depressive-like state through the mitigation of inflammatory status, oxidative stress, and the activation of AMPK/SIRT1 signaling pathway.Keywords: SalB, depression, CMS, AMPK/SIRT1